Analysis of the Effectiveness of Procurement of Goods and Services and its Impact on Non-Tax State Revenue in Central Maluku Regency - Sri Djamilah; Erly Leiwakabessy; Maryam Sangadji (LP2M IAIN Palopo, 2026)
Government procurement of goods and services is a crucial instrument in supporting development effectiveness and improving the quality of public services, and is also linked to regional financial performance, including Non-Tax State Revenue (PNBP). However, in practice, procurement implementation still faces various obstacles that have the potential to reduce its effectiveness and the resulting economic benefits. This study aims to analyze the effectiveness of government procurement of goods and services and its impact on PNBP management in Central Maluku Regency. This study employed a mixed-methods approach with an explanatory sequential design. Quantitative data were obtained through questionnaires from 75 respondents, consisting of procurement officials, financial managers, internal supervisors, service providers, and service users. Data were analyzed using Likert-based descriptive statistics. Qualitative data were collected through in-depth interviews and documentation studies to strengthen the quantitative analysis. The variables analyzed included the procurement process, human resource quality, transparency and accountability, the use of information technology, and the effectiveness of non-tax state revenue (PNBP) management. The research results indicate that the effectiveness of goods and services procurement in Central Maluku Regency is generally considered quite good. The procurement process, human resource quality, and transparency and accountability play a positive role in supporting the effectiveness of PNBP management. However, challenges remain in terms of timeliness, technical capacity of the apparatus, and the quality of procurement results, which impact PNBP optimization and public satisfaction. These findings demonstrate the need to strengthen procurement governance to improve the quality of public services and regional financial performance